3-D high-fidelity hydrostructural optimization of cavitation-free composite lifting surfaces. (15th July 2021) - Liao, Yingqian; Martins, Joaquim R.R.A.; Young, Yin Lu
Abstract: Design and manufacturing technologies have promoted the use of composites in hydrodynamic lifting surfaces. Composites, even with state-of-the-art coatings, are susceptible to cavitation erosion damage. This work aims to design a cavitation-free composite lifting surface to maximize efficiency while ensuring structural integrity. We optimize a canonical hydrofoil using a gradient-based optimization framework that couples a Reynolds-averaged Navier–Stokes solver with a finite-element structural solver. The optimization reduces the weighted drag coefficient by 1.2% over lift coefficients between 0.2 and 0.6, and increases the cavitation inception speed by 82% at the nominal condition compared to the baseline. The optimized design shows higher cavitation inception speeds than an Eppler hydrofoil (E1127, known for cavitation-free operation at moderate lift conditions) with the same baseline planform at C L ≥ 0.2 . The improvement from the E1127 hydrofoil was due mostly to delaying tip vortex cavitation induced by 3-D effects. The optimization finds the fiber angle to balance the bend-twist coupling and modifies the directional strength to reduce the susceptibility to excessive deformation and material failure when sweep presents.